KOMPETENSI GURU PENGGERAK DAN IMPLENTASINYA TERHADAP PROSES KEGIATAN PEMBELAJARAN MATERI PUISI RAKYAT KELAS VII DI SMP NEGERI 1 BANTARKAWUNG - Noviyanti, Intan; Wakhyudi, Yukhsan (Universitas Peradaban, 2025)
This study aims to identify and analyze the competency of transformative teachers and their implementation in the process of learning activities on folk poetry material in class VII at SMP Negeri 1 Bantarkawung. This type of study used descriptive qualitative with a case study approach. The techniques of data collection used were observation, interviews and documents. The results of study were obtained from observations, interviews with the head of the curriculum, and transformative teachers at SMP Negeri 1 Bantarkawung regarding the competency of transformative teachers in leading the learning process. The results of the transformative teacher competency in leading the learning activity process were: 1) prepare a learning plan, 2) adjust the approach used so that students could integrate local cultural values, and 3) utilize various learning resources to facilitate learning. In conclusion, the transformative teacher has implemented its competence as a transformative teacher in the process of learning activities on folk poetry material in class VII has implemented competence in differentiated learning on folk poetry material. Keywords: competence, transformative teacher, folk poerty